Experimental simulation of nanosatellites heat modes - Zavadskaja, E. S.; Rassamakin, B. M.; Rogachov, V. A.; Khairnasov, S. M; Khominich, V. I. (Technology and design in electronic equipment, 2013)
The technology of thermal modes modelling for nanosatellite (NS) PolyITAN-1 has been developed and thermal vacuum tests have been carried out. The results have shown that the simulation of the NS orbit and space factors is correct and confirmed that NS nodes and elements are operable under the specified conditions.